«But Don't Quote Me on That»: How Ukrainian Top Media Characterized the Perception of Migration and Migrants - Yuzva, Liudmyla; Tashchenko, Anna (Волинський національний університет імені Лесі Українки, 2021)
Ukraine finds itself in the countries of the Global North, which means that it adopts the formulation of its typical research questions like the current migration research landscape. Existing research are heavily skewed towards the Global North, where governments and international organiza-tions increasingly fund them to inform policy development. Thus, migration provides the relevance of the study of discourses around the body of concepts on it. The article describes the subtexts of media characterising the perception of migration by migrants themselves and the perception of migrants by host side. With using the Mediateka tool, an automated sample of 39,000 reports on various groups of migrants was received in the TOP-15 of the Ukrainian media (print media, TV channels, informational online media) from 2015 to 2018. The sample consisted of 12,000 messages, every tenth of which was selected for further in-depth analysis. The research was based on qualitative content analysis and critical discourse analysis. The six steps were done: looking at the description of the migration as objective necessity, subjective aspiration and something meaningless, and looking at the description of migrants as decent people, indecent people and just people with some lifestyle. The latent meanings of the messages, where the leading Ukrainian media touched on the perception of migration and migrants, were divergent and contradictory; they could not become the basis for confidence in any permanent characteristics of the images of migrants. As one of the most interesting prospects for further research, it may be the test of whether those transmitted meanings, which are usually considered positive, can interfere with social integration, and vice versa – whether negative meanings can help it. This can be done on the basis of additional empirical research using quantitative methods, such as cluster analysis to check which groups media consumers might be divided into after receiving the information about migrants.
Keywords: migrant; discourse about migrants; media messages; qualitative content analysis; critical discourse analysis; 316.774+314.74